Self-regulated parallel process 3-D array microfabrication with metal direct-write. (September 2021) - Zhang, Yong; Lin, Yen-Po; Zhang, Xianyun; Zhang, Yifan; Guo, Jianjun
Highlights: A scalable parallel direct-write technique for complex 3D nano-structures is developed. Self-regulating mechanism based on the thermodynamic stability and cross-talking of high-density meniscus array extended the current serial 3-D printing-process into scalable parallel one. Curvilinear metal spirals array over 800 μm height and 50 μm spacing is realized. Abstract: Parallel process direct-write manufacturing of ultrahigh aspect ratio 3-D metal microstructures remains one of the ultimate challenges in 3-D manufacturing. Its development promises novel solutions for high density chip scale packaging and sorting that require precision microscale mechanical and electrical interfaces to microelectronics. Herein, we exploited a self-regulated growth mechanism revealed in the meniscus-confined direct-write electro-deposition to realize the parallel process fabrication of high-density area arrays of ultrahigh aspect-ratio metal microwire structures. We demonstrated the direct-write fabrication of an array of curvilinear metal spirals over 800 μm in height and 50 μm in array spacing, structurally and mechanically appropriate for high density wafer probe testing applications that cannot otherwise be fabricated with any other existing methods. Graphical abstract: Self-regulated growth mechanism enables nozzle array-based parallel process direct-write of high density 3-D metal electronic microwires. Image, graphical abstract